Ghana in records from colonial missionaries, 1886-1951. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2010)
As outlined in the short history entitled The beginning of Africanisation : the dawn of the missionary motive in Gold Coast education by F.L. Bartels, the SPG's mission was originally established at Cape Coast Castle in 1752 by Rev. Thomas Thompson, who was succeeded by Rev. Philip Quaque, the first African to be ordained a priest of the Church of England. The mid-nineteenth century saw the revival of Anglican activity with the arrival of missionaries sent by the Mission of the West Indian Church to West Africa, based in Barbados. The period from 1903 onwards is the most substantially documented in this collection, recording the amalgamation of the missions for the Gold Coast, Sierra Leone and Nigeria, the spread of English education, the introduction of education for women and the development of missionary work in an ever-widening area. Records relating to the first 150 years are reproduced in both the Early colonial and missionary records from West Africa and the West Indies material in the archives of the USPG, 1710-1950. From the archives of the United Society for the Propagation of the Gospel, now held at Rhodes House Library, Oxford.
Date range: 1886-1951.
Keywords: Missionaries -- Ghana; Missions -- Ghana